1988
DOI: 10.1210/endo-123-1-505
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Synthesis by Isolated Rabbit Neurons*

Abstract: Insulin has been identified in the central nervous system of a number of vertebrate species, but the site of synthesis as yet remains unresolved. Two previous studies reported the presence of insulin mRNA in neural tissue, but related efforts to confirm and better localize the cellular origin of the hormone have yielded equivocal results. In the present study we have attempted to clarify this issue by employing both immunocytochemistry and in situ hybridization on isolated enriched cultures of rabbit brain neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…Moreover, some studies tried to further localize the cellular origin of insulin in the CNS and showed that the synthesis of insulin is confined to a subset of neurons and not glia [55]. In another study conducted in primary neuronal cell culture, Clarke et al have shown that depolarization of neuronal cells from rat brain by potassium ions in the presence of calcium or by veratridine caused more than threefold stimulation of release of immunoreactive insulin [56].…”
Section: Central Sourcementioning
confidence: 99%
“…Moreover, some studies tried to further localize the cellular origin of insulin in the CNS and showed that the synthesis of insulin is confined to a subset of neurons and not glia [55]. In another study conducted in primary neuronal cell culture, Clarke et al have shown that depolarization of neuronal cells from rat brain by potassium ions in the presence of calcium or by veratridine caused more than threefold stimulation of release of immunoreactive insulin [56].…”
Section: Central Sourcementioning
confidence: 99%
“…In invertebrates which lack an endocrine pancreas, insulin-related molecules have been described mainly in the central nervous system (Smit et al, 1988;Kromer-Metzger et al, 1994;Pimentel et al, 1996;Wolkow et al, 2000). In vertebrates, insulin or insulin-like transcripts have been found for instance in rat periventricular hypothalamic cells, in rabbit or rat neuron cell cultures and in an human neuroectodermal tumor (Young, 1986;Schechter et al, 1988;Nakamura et al, 2001).…”
Section: Choroid Plexus As Ins2 Expression Site In the Brainmentioning
confidence: 99%
“…(17). Neurons have been reported to synthesize insulin in neonatal rabbit brain (24). IGF-I mRNA was detected in whole rat brain at embryonic day 14 (25) and found in both neuronal and glial cultures of rat fetuses (25,26), although it was not detected in human fetal cerebral cortex (27).…”
Section: Specificity and Scatchard Analysis Of Inbulin And Igf-imentioning
confidence: 98%